KERAGAMAN ANOPHELES DI DESA SUNGAI TUHU DAN DESA PURWODADI OKU TIMUR TAHUN 2012 - Santoso, Santoso; Taviv, Yulian (Badan Penelitian dan Pengembangan Daerah Provinsi Sumatera Selatan, 2013)
Malaria in East OKU Regency remains a health concern. The number of cases as 980 clinical and 826 malaria positive. The highest number found in the Purwodadi health center with a number of 510 clinical cases (AMI =13.19 ‰ and API=8.37 ‰). One factor that may increase the risk of malaria infection is the presence of mosquitoes that are vectors of malaria, so we need a survey to know the vector species and its bionomic. Activity survey conducted in two villages in the district of East OKU, the Village and Village Purwodadi Tuhu River. Activities include the arrest of a 12-hour adult mosquito larvae and arrests around the houses. Results catching mosquitoes in the village of River Tuhu gained 15 Anopheles mosquitoes which consists of 7 species, namely: An.barbirostris, An.barbumbrosus, An. umbrosus, An.vagus, An.letifer, An.nigerimus and An.teselatus. Results catching mosquitoes in Purwodadi get 102 Anopheles mosquitoes which consists of 3 species, namely: An.barbirostris, An.barbumbrosus and An.vagus. Types of mosquito breeding sites are found in the form: the former pond, unused irrigation channels and rice fields.